Fracture behaviour of heat cured fly ash based geopolymer concrete - Sarker, Prabir; Haque, R.; Ramgolam, K. (Elsevier Ltd, 2013)
Use of fly ash based geopolymer as an alternative binder can help reduce CO 2 emission of concrete. The binder of geopolymer concrete (GPC) is different from that of ordinary Portland cement (OPC) concrete. Thus, it is necessary to study the effects of the geopolymer binder on the behaviour of concrete. In this study, the effect of the geopolymer binder on fracture characteristics of concrete has been investigated by three point bending test of RILEM TC 50 - FMC type notched beam specimens. The peak load was generally higher in the GPC specimens than the OPC concrete specimens of similar compressive strength. The failure modes of the GPC specimens were found to be more brittle with relatively smooth fracture planes as compared to the OPC concrete specimens. The post-peak parts of the load-deflection curves of GPC specimens were steeper than that of OPC concrete specimens. Fracture energy calculated by the work of fracture method was found to be similar in both types of concrete. Available equations for fracture energy of OPC concrete yielded conservative estimations of fracture energy of GPC. The critical stress intensity factor of GPC was found to be higher than that of OPC concrete. The different fracture behaviour of GPC is mainly because of its higher tensile strength and bond strength than OPC concrete of the same compressive strength.